PREDICTING THE FINANCING IMPACT OF THE GENERAL BUDGET ON PUBLIC DEBT ACCUMULATION IN IRAQ FOR THE PERIOD (1990-2023) - Researcher: Safa Rabih Abdul Hassan; Prof. Dr. Abbas Kazim Al-Dami; Assist Prof. Dr. Hashim Jabbar Al-Hussaini (Scholars Digest Publishing, 2025)
The general budget in Iraq has witnessed a clear fluctuation due to the suffering of the Iraqi economy and the deficit in the general budget resulting from the inability of public revenues to cover public expenditures and the spread of financial and administrative corruption. Hence, the state resorted to public debt as one of the means of financing the deficit in the general budget. Accordingly, the study addressed the clarification of the theoretical aspect of the general budget and public debt and reached results that there is no joint integration, i.e. the absence of a long-term equilibrium relationship between financing the general budget from public revenues and the accumulation of public debt.
Keywords: General budget financing, budget deficit, GDP deficit, public debt, ARDL.